2014
DOI: 10.1111/and.12300
|View full text |Cite
|
Sign up to set email alerts
|

High frequency ofTTTY2-like gene-related deletions in patients with idiopathic oligozoospermia and azoospermia

Abstract: Genes located on Y chromosome and expressed in testis are likely to be involved in spermatogenesis. TTTY2 is a Y-linked multicopy gene family of unknown function that includes TTTY2L2A and TTTY2L12A at Yq11 and Yp11 loci respectively. Using PCR amplification, we screened for TTTY2L2A- and TTTY2L12A-associated deletions, in 94 Greek men with fertility problems. Patients were divided into three groups as following: group A (n = 28) included men with idiopathic moderate oligozoospermia, group B (n = 34) with idio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
(91 reference statements)
1
5
1
Order By: Relevance
“…Perhaps their implication in male infertility might be more important than AZF genes which are routinely screened. A similar frequency of microdeletions of TTY2L2A and TTY2L12A genes is reported in oligoazoospermia and azoospermia patients form Greek patients [26]. The authors of this paper also concluded the involvement of these genes in spermatogenesis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Perhaps their implication in male infertility might be more important than AZF genes which are routinely screened. A similar frequency of microdeletions of TTY2L2A and TTY2L12A genes is reported in oligoazoospermia and azoospermia patients form Greek patients [26]. The authors of this paper also concluded the involvement of these genes in spermatogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly specific STSs were used for TTY2L12A and TTY2L2A regions with SRY (Metabion, Germany) as internal control. The primers used in this study have been previously used by Yapijakis et al [26]. Moreover, a blast search of the primer sequences showed that they were specific for the intended targets.…”
Section: Screening For Microdeletions In Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 208 unrelated men of Greek origin were investigated in this study: 108 men with fertility problems and 100 fertile men who served as normal controls. A collection of samples of semen and blood was conducted in the years 2002-2004 at the Department of Fertility, Bioerevna Diagnostic Center (Athens, Greece), after informed consent (14). All men participating had a full clinical, hormonal and semen evaluation and were considered to be infertile or normal according to the WHO recommendations of 1999 (13).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of factors may lead to aberrant spermatogenesis including chromosomal aberrations, Y-chromosome microdeletions, gene defects, hormonal abnormalities including diabetes, genital infection, as well as chemical and physical agents (14).…”
Section: Abstract Background: Thrombophilia-related Mutations Such mentioning
confidence: 99%